Determinants of Food Taboos in the Pregnant Women of the Awabel District, East Gojjam Zone, Amhara Regional State in Ethiopia - Wollelaw Getnet; Wubie Aycheh; Taddele Tessema (Advances in Public Health)
Background. Food taboos have great effect on pregnant women through prohibited essential food and/or drinks. It is transferred from generation to generation and has negative effect on pregnant mothers' health. Objective. To assess magnitude of food taboo and associated factors among pregnant women attending antenatal care at public health institutions in Awabel district, Northwest Ethiopia, 2016. Methods. Institutional based cross-sectional study was conducted. Three hundred seven pregnant women were selected for the study. All governmental health institutions in the district were included for the study. Data were entered in to Epi-Data version 3.1 and exported to SPSS version 20 for analysis. Multiple logistic regression analysis was conducted to identify independent predictors of food taboo. Results. Twenty-seven percent of pregnant mother encountered food taboos. Avoided food items by pregnant mothers were linseed, coffee, tea, cabbage, porridge, wheat bread, banana, pimento, groundnut, salty diet, nug, sugarcane, pumpkin, and coca drinks. Reasons mentioned for avoidance of this food items were plastered on the fetal head, making fatty baby which is difficult for delivery, fear of abortion, and fetal abnormality. Age of the mother AOR= 2.97 (1.71-5.16), income AOR= 0.28 (0.11-0.72), and previous antenatal care AOR= 2.33 (1.89-5.47) were significantly associated with food taboo. Conclusion. Our study revealed that considerable proportion of food taboo exists during pregnancy in the study area. This can be improved by strengthening the nutrition counseling components of antenatal care follow-up.